The seven moons of Maali Almeida : a novel - Karunatilaka, Shehan (W.W. Norton & Company, 2023)
"A searing satire set amid the mayhem of the Sri Lankan civil war. Colombo, 1990. Maali Almeida--war photographer, gambler, and closet queen--has woken up dead in what seems like a celestial visa office. His dismembered body is sinking in the serene Beira Lake and he has no idea who killed him. In a country where scores are settled by death squads, suicide bombers, and hired goons, the list of suspects is depressingly long, as the ghouls and ghosts with grudges who cluster round can attest. But even in the afterlife, time is running out for Maali. He has seven moons to contact the man and woman he loves most and lead them to the photos that will rock Sri Lanka. Ten years after his prize-winning novel Chinaman established him as one of Sri Lanka's foremost authors, Shehan Karunatilaka is back with a "thrilling satire" (Economist) and rip-roaring state-of-the-nation epic that offers equal parts mordant wit and disturbing, profound truths"--